A novel combined heat and water (CHW) technology applied in China northern coastal regions: Actual demonstration project towards promoting. (1st April 2022) - Li, Ziyong; Fu, Lin; Liu, Haochen
Highlights: The novel CHW technology can supply freshwater and clean heat economically. A new HW-CoP is proposed to produce hot freshwater with lower consumption and cost. HW-CoT can reduce heating transportation costs by up to 40%. The first project consistently produced hot freshwater free of contaminants. CHW system can supply heat to China's northern areas 200 ∼ 300 km from coastline. Abstract: Desalination and cogeneration technology for coastal thermal power plants can address severe lack of freshwater and clean heat sources in northern China. However, achieving high productivity, high efficiency and low cost simultaneously is a great challenge for the practical applications of both technologies. In this study, a novel combined heat and water (CHW) system is proposed that combines a district heating system with a freshwater supply system. Compared with previous studies, this study further improves the system efficiency, production capacity and reduces the cost. A practical demonstration project was established at a coastal nuclear power plant in northern China, including a heat-water co-production (HW-CoP) device, a heat-water co-transport (HW-CoT) pipeline and a heat-water separation (HW-SeP) device. A HW-CoP unit can produce 5 tons/hour of freshwater at 95 °C, which fully demonstrates the feasibility and verifies the practical performance of HW-CoP technology. Then, HW-CoT can reduce the heating transportation cost by 40% compared with the conventional heating mode and HW-SeP can further increase the heating supply capacity of the system by 50% compared with the plate heat exchanger. The results show that the new CHW system can consistently produce purer hot freshwater, which means the technologies are fully feasible in practical. Meanwhile, the novel CHW system has an economic heating radius of even more than 350 km compared to gas-fired boilers. In the future, through the use of the new CHW system, the waste heat from coastal power plants in northern China can meet the heating needs of a total of 5 billion square meters of buildings in cities 200–300 km from the coastline and supply more than 3.5 billion tons of freshwater per year, which has a broad application prospect. This paper can be used as a basis to further improve and optimize the district heating system and freshwater supply system in coastal areas.